VOMO LUDENS : Mechelen Meubelen : 25 jaar voortgezette opleiding meubelontwerp. - Vanderveken, Thomas; Laporte, Katrien; Van Den Storm, Dieter; Bernaerts, Peter; Wynants, Dirk (Mechelen : Thomas More, 2024)
Ruys, Stijn ; Van Vossel, James ; Moureau, Kathleen ; Vanderjonckheijd, Vincent ; De Becker, An ; De Meyer, Peter ; Lefever, Margot ; Segers, Bob ; Blondeel, Jonas ; Geenen, Geraldine ; Callewaert, Sven ; De Smul, Ingrid ; Van Mulders, Julie ; Keukelier-Moupila, Mieke ; Vermeylen, Oskar ; Van Eijk, Pim ; Welleman, Vincent ; Verhaegen, Yves ; Gielen, Geert-Jan ; Crabbe, Antoon ; Storms, Ben ; Jacobs, Jan ; Brock, Nicole ; Van den Poel, Pieter ; Couwenberg, Joop ; Vrinzen, Mark ; Defrancq, Wouter ; Vanderstraeten, Zoë ; Tettelin, Iona ; Engels, Jonathan ; Haerinck, Jana ; Van Helvoort, Robin ; Goyvaerts, Sam ; Devriendt, Edouard ; Proost, Anton ; Standaert, Barbara ; De Wit, Daan ; Verbist, David ; Lootens, Maurann ; Kuijpers, Gijs ; Schoenaers, Enzo ; Vandevenne, Manu ; De Korte, Quinten ; Scarcériaux, Thibeau ; De Jonckheer, Thomas ; Persyn, Wouter ; Van Deursen, Jens ; Lindelauf, Jord ; Doorenbos, Marit ; Smits, Thijs ; Pauwels, Bram ; Cornette, Hanne ; T'joen, Mara ; Fierens, Bent ; Van Hoeck, Caroline ; Pellens, Casper ; Peeters, Marnix ; De Koninck, Tom ; Platt, Joe ; Bollen, Jasper ; Vandeweege, Lukas Miel ; Timmerman, Yanni ; Boone, Fauve ; Schellen, Laura ; Van Orshaegen, Elias ; Vertommen, Axelle ; De Rouck, Hannah ; Frencken, Tom ; Vranken, Tim ; Storms, Ben
boek